Environmental ergonomics Commercial kitchens in a semi-tropical city - Gangiah, Sasi (AOSIS, 2022)
This book focuses on the environmental ergonomics of restaurant kitchens and the challenges related hereto in a semitropical city from a chef's perspective. It establishes the urgent need for commercial kitchens to be conducive to the well-being of kitchen workers as heat illness is unreported in this industry. This research is relevant from an occupational health and safety point of view. It evaluates the indoor environmental quality (IEQ) parameters such as heat, ventilation and humidity, noise and lighting in kitchens, cognisant that with different cuisines, the kitchen loads are different. The goals of occupational safety are health intervention for worker comfort to enhanced work performance. The book generates new knowledge regarding the factors affecting the body mass index of kitchen workers, prediction of heat and humidity near cooking stoves, discomfort near ovens, lighting in preparation areas and factors affecting reaction to stove noise. The book implements an exploratory design with multiple case studies.